Highly ordered 3D macroporous scaffold supported Pt/C oxygen electrodes with superior gas-proton transportation properties and activities for fuel cells - Li, J.; Tang, H.; Chen, R.; Liu, D.; Xie, Z.; Pan, M.; Jiang, San Ping (2015)
© The Royal Society of Chemistry 2015. An oxygen electrode finds many applications in various electrochemical energy conversion devices such as fuel cells and metal-air batteries. Highly efficient gas-proton transportation at the electrode is very important to enhance the power density of these devices. Herein, we report the construction of a highly efficient oxygen electrode with substantially improved proton conductivity and gas transportation properties using three dimensionally ordered macroporous Nafion/Cs2.5H0.5PW12O40, 3DOM Nafion/CsHPW, scaffold supported Pt/C nanocomposites. The best results were obtained for cells with 3DOM Nafion/CsHPW with 10% CsHPW, achieving a maximum power density of 955 mW cm-2, 31% higher than 730 mW cm-2 for the cell with the conventional Nafion-binder based oxygen electrode. The proton conductivity of the 10% 3DOM Nafion/CsHPW catalyst layer is 1.56 × 10-2 S cm-1, 112% higher than 7.35 × 10-3 S cm-1 measured for the conventional catalyst layer with the Nafion binder. The results demonstrate the significant advantages of the oxygen electrodes with the Pt/C-3DOM Nafion/CsHPW architecture over the conventional Nafion-binder based ones, with the significantly enhanced proton conductivity of uniformly distributed CsHPW nanoparticles (NPs) and much better gas diffusion properties of the 3DOM architecture.